2020
DOI: 10.1007/s00216-020-02840-0
|View full text |Cite
|
Sign up to set email alerts
|

Integrated graphene quantum dot decorated functionalized nanosheet biosensor for mycotoxin detection

Abstract: Decoration of graphene quantum dots (GQDs) on molybdenum disulfide (MoS 2 ) nanosheets serves as an active electrode material which enhances the electrochemical performance of the analyte detection system. Herein, ionic surfactant cetyltrimethylammonium bromide (CTAB)-exfoliated MoS 2 nanosheets decorated with GQD material are used to construct an electrochemical biosensor for aflatoxin B1 (AFB1) detection. An antibody of AFB1 (aAFB1) was immobilized on the electrophoretically deposited MoS 2 @GQDs film on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…A label-free electrochemical ultrasensitive biosensor was fabricated for AFB1 detection using MoS2@GQDs as an electrode surface transducer material. The immunosensor via the electrochemical method showed a signal response in the AFB1 concentration range of 0.1 to 3.0 ng/mL in a spiked maize sample with a detection limit of 0.09 ng/mL [70].…”
Section: Smart Sensors Based On Antibodiesmentioning
confidence: 99%
“…A label-free electrochemical ultrasensitive biosensor was fabricated for AFB1 detection using MoS2@GQDs as an electrode surface transducer material. The immunosensor via the electrochemical method showed a signal response in the AFB1 concentration range of 0.1 to 3.0 ng/mL in a spiked maize sample with a detection limit of 0.09 ng/mL [70].…”
Section: Smart Sensors Based On Antibodiesmentioning
confidence: 99%
“…As another strategy for electrode modification, quantum dots as zero-dimensional nanomaterials with negligible size and extremely high surface-to-volume ratio are excellent nanomaterials. Quantum dot-based electrodes could be used to enhance the sensitivity of aflatoxin B1—a toxin produced by fungus occurring in food, i.e., grains, peanuts, maize, and groundnuts—detection in maize samples with a detection limit of 0.09 ng/mL [ 197 ]. The quantum dots@porous carbon platform for the electrochemical detection of oxytetracycline—an antibiotic—was developed by Lin et al with the limit of detection of 3.23 × 10 −9 mol/L [ 198 ].…”
Section: Nanotechnology In Food Monitoringmentioning
confidence: 99%
“…The antibodies are immobilized by several techniques including covalent binding, self-assembly and electrostatic deposition, in which the covalent binding technique is often used due to the uniform immobilization of antibody attained through the amide bond formation between carboxylic acid groups on CNMs and amine groups on antibodies [ 22 ]. Prior to antibody immobilization, the carboxy-functionalized CNMs are usually activated using 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide/N-hydroxy succinimide (EDC/NHS) coupling/activating agent for effective binding of antibody on the electrode surface [ 35 38 ]. Different electrodes employed include glassy carbon electrode (GCE), carbon screen printed electrode (CSPE), carbon electrode (CE), indium tin oxide electrode (ITO), dispense printed electrode (DPE) and GO-based microelectrode, while differential pulse voltammetry (DPV), cyclic voltammetry (CV), amperometry (AMP), electrochemical impedance spectroscopy (EIS), alternating current voltammetry (ACV) and linear sweep voltammetry (LSV) are among the electrochemical detection systems frequently used [ 23 ].…”
Section: Electrochemical Immunosensors Based On Carbon Nanomaterialsmentioning
confidence: 99%
“…In two different studies by the same research group, GQDs conjugated with AuNPs or MoS 2 nanosheets were reported to enhance the electrochemical immunosensing performance for sensitive detection of AFB1 in maize samples [ 37 , 38 ]. In the former study, the GQDs-AuNPs nanocomposite fabricated through conjugation of carboxyl groups of GQDs and amino groups of the crosslinker 2-aminothiophenol was dispersed on an ITO electrode and subsequently immobilized with AFB1 antibody for AFB1 detection in maize samples [ 37 ].…”
Section: Electrochemical Immunosensors Based On Carbon Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation